Penyusunan Laporan Keuangan Pondok Pesantren Darul Mujawiddin Berdasarkan Pedoman Akuntansi Pesantren - Dinanti, Santya Dara; Fitriyah, Nur (Fakultas Ekonomi dan Bisnis Unram, 2025)
This research aims to analyze and evaluate the preparation of financial reports at the Darul Mujawiddin Islamic boarding school which has not implemented the Islamic Boarding School Accounting Guidelines. This research uses a descriptive quantitative approach with data collection techniques through observation and documentation studies. Research subjects include Islamic boarding school financial managers and administrators involved in the financial administration process. The research results show that the Islamic boarding schools studied still use simple financial recording methods and have not prepared financial reports in accordance with the Islamic Boarding School Accounting Guidelines. Many Islamic boarding schools still use manual cash books without a clear separationbetween restricted and unrestricted funds, and do not prepare financial position reports, cash flow reports and activity reports in a structured manner. Some of the obstacles found were limited knowledge about accounting, lack of trained human resources, and minimal technological support for financial recording and reporting. This research recommends that Islamic boarding schools improve their understanding of accounting through training, adopt a better recording system, and ensure that there is assistance in implementing the Islamic Boarding School Accounting Guidelines so that the financial reports prepared can meet applicable standards.